(3EfYcGSGJ GdCdYGH GdUZjQI Ydi Zge GdegGQGJ GdMQcjI deQMdI GdJYdje GdeJhSW aj GdLRGFQs - (3YHO GdYRjR, SGSjs; (3eMfO Ccdj(B, (3Hf Ycjs; (3eYgO GdJQHjI GdHOfjI h GdQjGVjI, LGeYI GdLRGFQ (B3 s ((3GdLRGFQ s, 2008)
(3EMJhi HMKfG Ydi OQGSI GddYH h GdCdYGH GdUZjQI h EfYcGSgG Ydi JYde GdegGQGJ GdMQcjI deQMdI GdJYdje GdeJhSW aj GdLRGFQ(B. (3MjK EYJeOfG aj gPG GdHMK Ydi ESJYeGd GdCdYGH GdUZjQI cCOGJ JYdjejI dHYV GdegGQGJ GdMQcjI h cPdc EHQGR CgejI GdeQMdI GdYeQjI h eOi aYGdjJgG aj fLGM GdegGQGJ GdMQcjI h cPdc EHQGR GdbjeI GdYdejI ddCdYGH GdUZjQI(B. (3h cPdc eYQaI eOi JCKjQ GdCdYGH GdUZjQI Ydi eYfhjGJ GdJdGejP aj gPg GdeQMdI(B. (3h aj GdCNjQ JhUdfG Edi GdOhQ GdPj JdYHg GdCdYGH GdUZjQI aj JYde GdegGQGJ GdMQcjI deQMdI GdJYde GdeJhSW aj GdLRGFQ(B.s
(3eGLSJjQs
Keywords: (3GdCdYGH GdUZjQIs; (3GdJYdes; (3GdegGQGJ GdMQcjIs; (3GdfTGW GdHOfj GdQjGVj GdJQHhjs